2013
DOI: 10.1038/pcan.2013.54
|View full text |Cite
|
Sign up to set email alerts
|

Anterior tumors of the prostate: clinicopathological features and outcomes

Abstract: Despite the potential for adverse pathological features in anterior-based disease, there appears to be no demographic predilection, notable delay in diagnosis or significant difference in survival outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 12 publications
4
38
4
Order By: Relevance
“…Another consideration regarding the applicability of our data is that that the patients with cT1/T2 (hence no clinical ECE) and occult T3b disease may represent a special subset of patients with SVI. For example, these patients may be more likely to have anterior tumors, which are more difficult to clinically evaluate [35], than what an average cT3 patient has.…”
Section: Discussionmentioning
confidence: 96%
“…Another consideration regarding the applicability of our data is that that the patients with cT1/T2 (hence no clinical ECE) and occult T3b disease may represent a special subset of patients with SVI. For example, these patients may be more likely to have anterior tumors, which are more difficult to clinically evaluate [35], than what an average cT3 patient has.…”
Section: Discussionmentioning
confidence: 96%
“…2,7 Some authors state that these PC tend to have lower Gleason scores (GS) and are less likely to demonstrate unfavorable pathologic outcomes, whereas others did not find any association between tumor zone origin and biochemical recurrence after treatment with curative intention. 2,8,9 Similarly, tumor volume (TV) of TZ/AFMS PC is discussed controversially. Although Ouzzane et al 7 postulate that most tumors are small with a median TV of o2 cm 3 , Mygatt et al 2 analyzed 1528 radical prostatectomy (RP) specimen, postulating higher TV compared with that in PZ tumors.…”
Section: Introductionmentioning
confidence: 98%
“…Surgical specimens, however, show that a considerable amount of diagnosed cancers are located in TZ and AFMS (Supplementary Figure 1). 2,3,6,7 Anterior tumors are often not palpable in digital rectal examination (DRE) and tend to have higher PSA levels. 2,7 Some authors state that these PC tend to have lower Gleason scores (GS) and are less likely to demonstrate unfavorable pathologic outcomes, whereas others did not find any association between tumor zone origin and biochemical recurrence after treatment with curative intention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their study included men with advanced PCa (pT3, pT4) that is associated with higher PSA levels than those of organ-confined PCa (pT2). The subpopulation with posterior PCa had furthermore a wide range of PSA levels (0.003-5065 ng/ml) than the subpopulation with anterior PCa (1.12-69.0) 17 . Another study including men with advanced PCa and lymph node metastasis revealed that anterior PCa had a higher PSA level than posterior PCa, but the difference in PSA levels between those PCa groups was not significant 20 anterior apical biopsies to a standard 12-core biopsy achieved a higher rate of cancer detection than a 12-core scheme and unique cancer detection when all regions were considered 21 .…”
Section: Discussionmentioning
confidence: 99%